2018
DOI: 10.1088/1748-9326/aac3e5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in climate extremes over West and Central Africa at 1.5 °C and 2 °C global warming

Abstract: In this study, we investigate changes in temperature and precipitation extremes over West and Central Africa (hereafter, WAF domain) as a function of global mean temperature with a focus on the implications of global warming of 1.5 • C and 2 • C according the Paris Agreement. We applied a scaling approach to capture changes in climate extremes with increase in global mean temperature in several subregions within the WAF domain: Western Sahel, Central Sahel, Eastern Sahel, Guinea Coast and Central Africa includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 62 publications
9
65
0
2
Order By: Relevance
“…The length of consecutive wet days (CWD) decreases over the western and eastern Sahel (Figure 6b), while the consecutive dry days (CDD) increase mainly over the Sahel (western, central and eastern) ( Figure 6c) in consistence with [60]. These results are consistent with recent studies comparing incidences of 1.5 • C and 2 • C global warming level [61,62] and showing a reduction in mean rainfall for the models with enhanced warming level. They confirm also the significant increase of the length of consecutive dry days over the Western Sahel (Senegal) found in most global models [61] and regional models [62].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The length of consecutive wet days (CWD) decreases over the western and eastern Sahel (Figure 6b), while the consecutive dry days (CDD) increase mainly over the Sahel (western, central and eastern) ( Figure 6c) in consistence with [60]. These results are consistent with recent studies comparing incidences of 1.5 • C and 2 • C global warming level [61,62] and showing a reduction in mean rainfall for the models with enhanced warming level. They confirm also the significant increase of the length of consecutive dry days over the Western Sahel (Senegal) found in most global models [61] and regional models [62].…”
Section: Resultssupporting
confidence: 90%
“…The RegCM4 model simulates an increase of the Warm Spell Duration Index in the whole Sahel domain and over the Guinea Coast (Figure7f). These results are in agreement with intensification of thermal extremes over Sahel and of heat waves in the Guinea Coast with increase of global temperature found in [61] and comparing changes in temperature extremes between 1.5°C and 2°C global warming over West Africa. The temperature indices considered in this study are: TX90P (the very warm days), TN90P (the warm nights) and WSDI (the warm spell duration index).…”
Section: Resultssupporting
confidence: 90%
“…Such a warming is expected to affect precipitation and its variability, especially drought and flood episodes, in both the tropics and the subtropics (Zwiers et al, 2013;Giorgi et al, 2014). Over West Africa, previous studies (Collins et al, 2013;Diedhiou et al, 2018;Bichet et al, 2019) have shown that the warming is expected to occur at a faster rate than the global average (+0.5 vs. +0.3 • C per decade). Future changes in precipitation however are still unclear (e.g., Collins et al, 2013;Sylla et al, 2016;Bichet et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Future changes in precipitation however are still unclear (e.g., Collins et al, 2013;Sylla et al, 2016;Bichet et al, 2020). Nevertheless, future changes in precipitation extremes are expected in some subregions, such as an increase in the maximum length of dry spells over West Sahel (Sylla et al, 2016;Diedhiou et al, 2018) and an intensification of extreme rainfall over the Guinea Coast (Diedhiou et al, 2018). Particu-larly relevant for agriculture, changes in precipitation are also projected during the growing season, expected to become shorter, as torrid, arid, and semiarid climate conditions are expected to extend (Sylla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Schleussner et al (2016) found a 2% increase in the intensity of heavy rainfall between a 1.5 and 2.0 C globally and a 3% increase over South Asia. However, Rogelj et al (2015) warned that limiting the warming to below 1.5 C may require greater mitigation efforts and higher mitigation costs than keeping it at 2.0 C. Over Africa, some studies found higher impacts at 2.0 C GWL than at 1.5 C (Diedhiou et al, 2018;Klutse et al, 2018;Maúre et al, 2018;Mba et al, 2018;Nikulin et al, 2018;Osima et al, 2018;Weber et al, 2018;Tamoffo et al, 2019). For example, Weber et al (2018) found that rainfall intensity is likely to increase under a higher global warming scenario, especially over the sub-Saharan coastal regions.…”
mentioning
confidence: 99%